The Review on the Science Process Skills and the Levels to Create a Graphic: The Sample on Preservice Science Teachers - Sibel Demir Kaçan; Nisa Yenikalaycı; Dilek Çelikler (Sakarya University Journal of Education)
In science education, drawing tables and graphics is a part of science process skills, and preservice teachers are expected to have these skills. The aim of this study is to examine the science process skills and create a graphic levels of preservice science teachers based on a given problem scenario. In the research, the survey method has been used. The research has been conducted with 87 preservice teachers in total who receive their education at the third grade in The Department of Science Education in a state university in Blacksea region. The worksheet which has been developed by the expert researchers in their field has been used in order to collect the data. 17 items and 3 aspects have been used in order that the data on this activity worksheet has been evaluated. The exact statements which include the scientific accuracy have been encoded as sufficient, the partly scientific accuracy have been encoded as partially sufficient, and the incorrect statements and the empty answers have been encoded as insufficient. According to the frequency distribution table which has been made as a result of the data, it has been determined that the preservice teachers are insufficient on the subjects of being able to show the data of variables in the scenario on the ready figures, to position the variables correctly onto the axes. According to the results obtained from the research, it is thought that other studies can be conducted on the subjects that the preservice teachers are partially sufficient and insufficient.